2019
DOI: 10.3390/cells8090957
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Chemotherapy Resistance in Triple-Negative Breast Cancer—How We Can Rise to the Challenge

Abstract: Triple-negative (TNBC) is the most lethal subtype of breast cancer owing to high heterogeneity, aggressive nature, and lack of treatment options. Chemotherapy remains the standard of care for TNBC treatment, but unfortunately, patients frequently develop resistance. Accordingly, in recent years, tremendous effort has been made into elucidating the mechanisms of TNBC chemoresistance with the goal of identifying new molecular targets. It has become evident that the development of TNBC chemoresistance is multifac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
514
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(523 citation statements)
references
References 201 publications
(282 reference statements)
2
514
0
7
Order By: Relevance
“…Since chemoresistance of TNBC is multifaceted, based on the interplay of drug efflux [67], apoptosis [68,69], cancer stem cell phenotype [17], tumor microenvironment [70], and multiple signaling pathways [71], the mechanism of chemoresistance in TNBC has to be analyzed under many different aspects. In the present study, characteristics of BCSCs under chemotherapeutic stress were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Since chemoresistance of TNBC is multifaceted, based on the interplay of drug efflux [67], apoptosis [68,69], cancer stem cell phenotype [17], tumor microenvironment [70], and multiple signaling pathways [71], the mechanism of chemoresistance in TNBC has to be analyzed under many different aspects. In the present study, characteristics of BCSCs under chemotherapeutic stress were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Their treatment depends on cytotoxic taxane-, anthracycline-, and platinum-based regimens that target cell-cycle progression. In approximately 20% of these patients, tumors will completely regress after such therapy (complete pathological response), but for those patients that do not achieve this level of response, the risk of reoccurrence and death from metastases are many fold more than for those with hormone-positive cancers [9,10]. Overall, 90% of breast cancer patients who develop metastatic disease become resistant to their chemotherapy regimens [11].…”
Section: Introduction-history Of Breast Cancer Current Management Amentioning
confidence: 99%
“…Despite the high heterogeneity and a plethora of molecular signatures, there are common mechanisms of chemotherapy resistance in triple-negative breast cancers, which have also become recognized in recent years to be associated with treatment failure against hormonal and HER2/neu targeted treatments [10,12]. By no means exhaustive, three of these mechanisms of interest in breast cancer research are ATP-binding cassette (ABC) transporters, cancer stem cells, and microRNAs.…”
Section: Introduction-history Of Breast Cancer Current Management Amentioning
confidence: 99%
“…In fact, Bcl-2 shows as well anti-autophagic activity by stabilizing lysosomal membrane and preventing lysosomal destabilization [100,101]. As a result, cancer cells, that express elevated Bcl-2 levels, are more chemoresistant to the standard treatments that activate either apoptosis or autophagic cell death [102,103]. Not surprisingly, we found that HepG2 cells upon NP treatment did not exhibit lysosomal dysfunction (Figure 5g) and destabilization (Figure 5f and Supplementary Figure S6).…”
Section: P53 Sub-cellular Localization Mediates Hepatic Cell Responsementioning
confidence: 76%